Task-Based Learning in the Classroom for EFL Learners: A Review - Muhammad Badrus Sholeh (Center of Language and Cultural Studies, 2020)
In language teaching and learning, there are several methodologies and approaches; one of them is TBL. Since the 1980s, this approach has had the most pedagogical attention in second language pedagogy. TBL is becoming increasingly common worldwide, particularly in English classes in Indonesia. The task's goal is to establish a clear reason for language use and create a natural meaning for language learning. The ideas and principles of TBL have proven to be effective in classrooms. This paper aims to explain why teachers should implement TBL (TBL) in the language classroom and how to implement TBL during classroom instruction. The discussion begins with the introduction and the description of TBL. Then, it goes on TBL characteristics and continues with the approaches, the benefits, and framework of TBL.